A method for treating ethyl acetate color

CN117700325BActive Publication Date: 2026-10-23ZHUHAI QIANXIN NEW MATERIALS CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202311728582.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-15
Publication Date
2026-10-23
Estimated Expiration
2043-12-15

AI Technical Summary

Technical Problem

[0008]本发明的目的是针对乙酸乙酯生产中发色物质组成复杂的问题,提供一种乙酸乙酯色度处理方法,通过物理方法和化学方法搭配使用逐步脱除多种发色物质,具有适用性强、脱色效率高和工艺简单的特点

Benefits of technology

[0047]1.本色度处理方法采用复配技术制备吸附剂,由凹凸棒土和丝光沸石按一定比例捏合成型后焙烧制得。凹凸棒土因具有独特的晶体结构而具有良好的吸附脱色能力,通过加入纳米碳粉经焙烧后造孔,在此基础上,进一步对凹凸棒土和沸石进行改性,接枝上大分子结构的纤维素,经改性后形成的吸附剂,对碳化物和金属离子具有很强的吸附能力。另外,制得的吸附剂在较高温度下可长期使用,脱色效果好,吸附过程物料损失少。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117700325B_ABST
    Figure CN117700325B_ABST
Patent Text Reader

Abstract

The present application relates to a kind of ethyl acetate colorimetry processing method, specifically by conveying pump the reaction kettle material of ethyl acetate esterification tower bottom is transported to adsorption tank, using compound adsorbent removes carbide and metal ions, then material enters decolorization reaction tank and removes carbonyl compound by nucleophilic addition reaction, finally the material after decolorization returns reaction kettle, make tower bottom reaction kettle material and tower top crude ester colorimetry reduce, ethyl acetate product colorimetry reaches the requirement of national standard superior product.The present application is combined with the method of physical adsorption and chemical reaction, using sulfuric acid and acetic acid to acid wash pretreatment, shaping preparation after attapulgite and mordenite, and graft macromolecular cellulose, form adsorbent, with excellent adsorption performance, the decolorization rate of material in tower bottom reaction kettle after physical adsorption and chemical method combination use is ≥80%, the ethyl acetate colorimetry processing method described in the present application is good for the decolorization effect of reaction kettle acidic material, can be applied to the industrialized production of ethyl acetate, improve product quality, reduce pollutant emission.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of ethyl acetate production technology, and specifically to a method for color treatment of ethyl acetate. Background Technology

[0002] Ethyl acetate is a colorless, transparent, free-flowing, flammable liquid with a fruity aroma. It is volatile and is mainly used as a solvent, with wide applications in pharmaceuticals, dyes, rubber, coatings, inks, and adhesives.

[0003] Industrially, acetic acid and ethanol are generally used for esterification to prepare ethyl acetate. However, the use of concentrated sulfuric acid as a catalyst in the esterification process can cause the organic matter to carbonize, producing colored substances that darken the color of the substances in the column. Excessively high reaction temperatures or prolonged reaction times can also lead to carbonization or even oxidation of the materials, increasing the color of the product and thus affecting product quality. Iron ions produced by the corrosion of equipment by concentrated sulfuric acid can also contribute to the color. Impurities in the raw materials and side reactions can also result in the presence of low-carbon carbonyl compounds in the material, such as butanedione, glutaraldehyde, 2,3-pentanedione, and 2,4-pentanedione, all of which are color-producing substances.

[0004] Besides reducing the generation of color-producing substances by controlling reaction temperature and time to maintain process stability, common methods include increasing the reflux ratio of the esterification distillation column to keep the color-producing substances at the bottom of the column or periodically discharging the bottom liquid. Environmentally friendly and energy-saving methods can also be used to decolorize the color-producing substances. Common decolorization methods include chemical and physical methods. Chemical methods require the introduction of new substances such as acids and alkalis, which increases the difficulty of subsequent processing and puts significant environmental pressure on the industry. Using strong oxidants such as hypochlorous acid and hydrogen peroxide for decolorization may oxidize the esterification products, further deepening the color. Physical methods mainly use adsorbents such as activated carbon for decolorization, which can lead to some product residue remaining in the activated carbon, resulting in product loss and increasing the amount of waste residue. Other methods include activated alumina adsorption, hydrogenation decolorization, bromic acid treatment, ion exchange resin methods, zeolite molecular sieve methods, and liquid-liquid extraction. Each of these decolorization technologies has its advantages and disadvantages. Due to the complex composition of color-producing substances in ethyl acetate production, using a single decolorization method is ineffective; therefore, methods need to be screened, optimized, and combined based on actual production conditions.

[0005] CN107597057A discloses an attapulgite clay decolorizing adsorbent for waste engine oil regeneration and its preparation method. It discloses the combined use of zeolite molecular sieves and attapulgite clay after sintering, resulting in a modified attapulgite clay decolorizing adsorbent with strong adsorption capacity and good decolorization effect. However, this invention does not mention adding nano-carbon powder as a pore-forming agent to improve the pore structure of the adsorbent, nor does it mention acid washing pretreatment of the zeolite molecular sieves and attapulgite clay.

[0006] CN1126197A discloses a method for removing carbonyl-containing impurities from α,β-unsaturated carboxylic acids. The method involves reacting bisulfite with the carbonyl group to generate the corresponding water-soluble sulfonate salt, thereby removing the carbonyl-containing impurities. However, this invention is only applicable to the removal of carbonyl compounds and cannot remove carbides and metal ions.

[0007] Therefore, there is an urgent need to propose a technical solution to improve the shortcomings of existing technologies. Summary of the Invention

[0008] The purpose of this invention is to address the problem of complex composition of chromogenic substances in ethyl acetate production by providing a method for treating the color of ethyl acetate. This method uses a combination of physical and chemical methods to gradually remove multiple chromogenic substances, and features strong applicability, high decolorization efficiency, and simple process.

[0009] The bottom reactor temperature in ethyl acetate production units is relatively high, making it easy for the material to carbonize and form colored substances. The temperature is even higher towards the bottom of the tower, increasing the likelihood of colored substance formation. Colored substances with boiling points lower than the bottom temperature vaporize and enter the tower, while those with higher boiling points are easily carried to the top, affecting the color of the crude ester and resulting in substandard color in the final ethyl acetate product. By controlling the distillation temperature and reflux ratio of the ethyl acetate esterification tower, high-boiling-point colored substances can be retained at the bottom and separated from the lighter components at the top, achieving or near-colorless crude ester color. However, when the generated colored substances have boiling points close to those of ethyl acetate, they are difficult to separate by distillation, impacting product quality. Therefore, decolorizing the material in the bottom reactor can significantly improve the color of ethyl acetate. This material has a complex composition, containing organic compounds such as acetic acid, ethanol, and ethyl acetate, as well as water, making it a highly acidic homogeneous oil-water mixture.

[0010] Attapulgite is a magnesium-rich fibrous mineral, mainly composed of silicon dioxide. It has a fine texture and a bluish-gray or grayish-white appearance. Attapulgite has good decolorizing properties; compared to activated clay, it requires less dosage, results in less oil loss, and is cheaper. The problem is that filtration is relatively difficult, so the fineness of the clay should be appropriately coarsened.

[0011] The chemical composition of zeolite adsorbents is mainly silicon dioxide, followed by aluminum oxide. Zeolite has a good decolorization effect, and during decolorization, it can also reduce the acid value and moisture content of oils. It is cheaper than activated clay and is a new material for oil decolorization.

[0012] The adsorbent prepared by compounding attapulgite and zeolite is granular, combining the advantages of both. Compared with kaolin and activated carbon, it is cheaper and requires less dosage, while exhibiting good decolorization effect. Furthermore, the attapulgite and zeolite are modified by grafting large-molecule cellulose. Cellulose has numerous hydroxyl groups, which is beneficial for the adsorption of polar substances such as organic matter and metal ions. Moreover, the large molecules of cellulose can penetrate well into the various pores, resulting in a large adsorption surface area. This improves the adsorption efficiency of the adsorbent and removes impurities as much as possible.

[0013] To address the issue that carbonyl compounds are difficult to adsorb and remove, this invention employs a chemical method to remove carbonyl compounds. Through nucleophilic addition reactions, colored carbonyl compounds can be rapidly removed with short reaction times, high removal efficiency, and easy product separation.

[0014] This invention discloses a method for color treatment of ethyl acetate, which includes the following steps:

[0015] The material is treated with an adsorbent in an adsorption tank, and then decolorized to obtain the finished product.

[0016] The adsorbent is a blend of modified attapulgite and modified zeolite.

[0017] The adsorbent is prepared by the following method:

[0018] S1. The blend of attapulgite and zeolite is immersed in a solution of sulfuric acid and acetic acid, then washed and dried, and then blended and shaped by an extruder and calcined at high temperature to obtain intermediate product 1.

[0019] S2. After washing the intermediate product 1, it is immersed in a mixed solution of sodium hydroxide and hydrogen peroxide, heated and stirred, washed and dried to obtain the surface-hydroxylated intermediate product 2.

[0020] S3. Immerse the product from step S2 in a carboxymethyl cellulose solution, heat and sonicate, and wash and dry to obtain the adsorbent.

[0021] Specifically, the material to be processed in the reactor is transported to the adsorption tank by a transfer pump, where a compound adsorbent is used to remove carbides and metal ions. Then, the material enters the decolorization reactor to remove carbonyl compounds through a nucleophilic addition reaction. Finally, the decolorized material is returned to the reactor, thereby reducing the color of the material at the bottom of the reactor.

[0022] Both the adsorption tank and the decolorization reaction tank operate at room temperature and pressure without the need for additional heating.

[0023] The specific decolorization process is as follows:

[0024] F1. Adsorption of solid carbides and metal ions: The material in the bottom reactor is transported by a pump from top to bottom through the fixed bed of the adsorption tank.

[0025] F2. Carbonyl Compound Removal: The material after passing through the adsorption tank enters the decolorization reaction tank. When the liquid level in the tank reaches 2 / 3 of its height, a prepared saturated sodium bisulfite solution (greater than 40% wt) is added to the decolorization reaction tank at a ratio of 10% wt of the material in the bottom of the tower. The solution is thoroughly mixed with the material. After 2-20 minutes, the decolorized mixture is sent to the phase separator for oil-water separation. The aqueous phase is discharged, and the wastewater is sent to the wastewater treatment system. The decolorized oil phase is returned directly to the bottom of the tower. The saturated sodium bisulfite solution used should be freshly prepared and should not be left for a long time, as it is easily oxidized to sodium bisulfate.

[0026] The color of the above materials was determined according to the national standard GB / T 3728-2007, and the decolorization rate was calculated using the following formula:

[0027]

[0028] In the formula:

[0029] Y—Decolorization rate of the material in the reactor;

[0030] B0—Original color of the material in the reactor;

[0031] B1—Color of the material in the reactor after decolorization.

[0032] in,

[0033] The volume of the adsorption tank is 3-10 m³. 3 The flow rate of the material in the reactor is 1-3 m / s. 3 / h;

[0034] The volume of the compound adsorbent filled in the adsorption tank is 2-4 m³. 3 The compound adsorbent is dispersed and piled in the tank to form a fixed bed;

[0035] The compound adsorbent is prepared by compounding attapulgite and mordenite. Attapulgite powder and mordenite powder are mixed in a certain proportion, and a certain amount of 30% silica sol and nano carbon powder are added. After being mixed evenly, the mixture is extruded and cut into cylinders. After drying at 105°C for 2 hours, the cylinders are placed in a muffle furnace for high-temperature calcination for a certain period of time and then cooled to room temperature to obtain the finished adsorbent. The attapulgite, mordenite, silica sol and nano carbon powder are all commercially available ordinary products.

[0036] Furthermore, the mass ratio of sulfuric acid to acetic acid is 1:1 to 1:3.

[0037] Specifically, the attapulgite and mordenite are pretreated with acid and water before use. They are then completely soaked in a mixture of 10-30 wt% sulfuric acid and 65-85 wt% acetic acid, heated to 60-80°C, and thoroughly mixed for 30-60 minutes. After filtration, they are washed with distilled water until neutral and dried for 2 hours before proceeding to subsequent processing.

[0038] Furthermore, the particle size of the attapulgite is 40-60 mesh; the particle size of the zeolite is 0.5-20 nm.

[0039] Furthermore, the mass ratio of the attapulgite clay to the zeolite is 2-4:1.

[0040] Furthermore, the intermediate product is a cylinder with a diameter of 5 mm and a length of 5-10 mm.

[0041] Furthermore, the calcination temperature is 250-550℃, and the calcination time is 2-6h.

[0042] Furthermore, in the decolorization process, sodium bisulfite solution is used to react with impurities in the material.

[0043] Furthermore, the mass ratio of the sodium bisulfite solution to the material is 0.1:10 to 1:10.

[0044] Furthermore, the sodium bisulfite solution is a saturated solution.

[0045] Furthermore, the adsorbent also includes silica sol and nano-carbon powder.

[0046] Compared with the prior art, the beneficial effects of the present invention are:

[0047] 1. The color treatment method employs a compounding technique to prepare the adsorbent, which is obtained by kneading attapulgite and mordenite in a certain proportion and then calcining. Attapulgite, due to its unique crystal structure, possesses excellent adsorption and decolorization capabilities. By adding nano-carbon powder and calcining to create pores, and further modifying the attapulgite and zeolite by grafting macromolecular cellulose, the resulting adsorbent exhibits strong adsorption capacity for carbides and metal ions. Furthermore, the prepared adsorbent can be used for extended periods at higher temperatures, demonstrating good decolorization effects and minimal material loss during the adsorption process.

[0048] 2. Surprisingly, both sulfuric acid and acetic acid were found in the reactor bottom material. Pre-treatment with a mixture of these two acids (sulfuric acid and acetic acid) can remove impurities such as metal ions soluble in acidic substances from attapulgite and mordenite, increasing the number of micropores and surface area, thereby improving adsorption performance. If no acid washing is performed, or if other types of acid are used, the reactor bottom material containing sulfuric acid and acetic acid will produce metal ion impurities soluble in sulfuric acid or acetic acid when it comes into contact with the adsorbent, affecting the adsorption and decolorization effect. Mixed acid washing can leverage the synergistic effect of the two acids, resulting in faster washing and reducing the acid concentration and treatment temperature required when using a single acid wash.

[0049] 3. This invention first employs physical adsorption to remove carbides and metal ions, which reduces the adverse effects of these impurities on subsequent chemical methods and facilitates rapid phase separation after the reaction of carbonyl compounds. The combined use of physical and chemical methods not only reduces the color of the material at the bottom of the ethyl acetate reactor but also reduces reactor waste, saves on wastewater treatment costs, ensures product quality, and enables the ethyl acetate product to meet the national standard for superior grade color. Furthermore, the operation is simple and can be performed continuously or intermittently. Attached Figure Description

[0050] Figure 1 Schematic diagram of the decolorization process of materials in the bottom reactor of ethyl acetate tower;

[0051] Attached diagram labels: 1 is the bottom reactor, 2 is the esterification tower, 3 is the adsorption tank, 4 is the decolorization reaction tank, and 5 is the phase separator. Detailed Implementation

[0052] To more clearly illustrate the technical solution of the present invention, the following embodiments are provided, but the present invention is not limited thereto.

[0053] Unless otherwise stated, the raw materials, reactions, and post-processing methods mentioned in the examples are all commercially available raw materials and technical methods well known to those skilled in the art.

[0054] In the embodiments and comparative examples of this invention, the number of parts refers to the number of parts by mass.

[0055] Example 1

[0056] A method for color treatment of ethyl acetate, comprising the following steps:

[0057] The material to be processed in the reactor is transported to the adsorption tank by a transfer pump. A compound adsorbent is used to remove carbides and metal ions. Then the material enters the decolorization reactor to remove carbonyl compounds through a nucleophilic addition reaction mechanism. Finally, the decolorized material is returned to the reactor, which reduces the color of the material at the bottom of the reactor.

[0058] in,

[0059] The volume of the adsorption tank is 3m³. 3 The flow rate of the material in the reactor is 2m. 3 / h;

[0060] The volume of adsorbent filled in the adsorption tank is 2m³. 3 The adsorbent is dispersed and piled inside the tank to form a fixed bed (the height of the bed is 2 / 3 of the height of the tank).

[0061] The above-mentioned adsorbent is a blend of modified attapulgite and modified zeolite, prepared by the following method:

[0062] S1. 60 parts of attapulgite clay (40 mesh particle size) and 20 parts of mordenite zeolite (10 nm particle size) were pretreated with acid and washed with water before use. They were then completely soaked in a mixture of 20 wt% sulfuric acid aqueous solution and 80 wt% acetic acid aqueous solution at a mass ratio of 1:1. The mixture was heated to 70°C and thoroughly mixed for 50 min. After filtration, the mixture was washed with distilled water until neutral and dried for 2 h. Then, 10 parts of 30 wt% silica sol and 15 parts of nano-carbon powder were added and mixed evenly. The mixture was then fed into a twin-screw extruder and extruded at high temperature. The resulting strip material was cut into regular cylinders with a diameter of 5 mm and a length of 5 mm. Finally, the cylinders were calcined in a muffle furnace at 400°C for 4 h to obtain intermediate product 1.

[0063] S2. Wash the intermediate product 1 with deionized water, then immerse 1 part of the intermediate product 1 in 100 parts of NaOH / H2O2 mixed solution, heat and stir under reflux at 80°C for 2 hours, filter, wash with ethanol and deionized water, and vacuum dry at 70°C for 8 hours to obtain the surface hydroxylated modified intermediate product 2.

[0064] S3. Immerse intermediate product 2 from step S2 in a carboxymethyl cellulose solution (50 wt%), heat to 80°C and sonicate for 2 hours, then wash and dry with water and ethanol to obtain the adsorbent.

[0065] Both the adsorption tank and the decolorization reaction tank operate at room temperature and pressure without the need for additional heating.

[0066] In the NaOH / H2O2 mixed solution, the concentrations of NaOH and H2O2 are 0.5 wt% and 2 wt%, respectively.

[0067] The specific decolorization process is as follows:

[0068] F1. Adsorption of solid carbides and metal ions: The material in the bottom reactor is transported from top to bottom through the fixed bed of the above adsorption tank by a transfer pump, and the residence time is 1 hour.

[0069] F2. Removal of carbonyl compounds: The material after passing through the adsorption tank enters the decolorization reaction tank. When the liquid level in the tank reaches 2 / 3 of the height, a freshly prepared saturated sodium bisulfite solution (40wt%) is added to the decolorization reaction tank at a ratio of 10wt% of the material in the bottom of the tower. The solution is then thoroughly mixed with the material. After 5 minutes, the decolorized mixture is sent to the phase separator for oil-water separation. The aqueous phase is discharged, and the wastewater is sent to the wastewater treatment system. The decolorized oil phase material is directly returned to the bottom of the tower.

[0070] Example 2

[0071] A method for color treatment of ethyl acetate, comprising the following steps:

[0072] The material to be processed in the reactor is transported to the adsorption tank by a transfer pump. A compound adsorbent is used to remove carbides and metal ions. Then the material enters the decolorization reactor to remove carbonyl compounds through a nucleophilic addition reaction mechanism. Finally, the decolorized material is returned to the reactor, which reduces the color of the material at the bottom of the reactor.

[0073] in,

[0074] The volume of the adsorption tank is 3m³. 3 The flow rate of the material in the reactor is 2m. 3 / h;

[0075] The volume of adsorbent filled in the adsorption tank is 2m³. 3 The adsorbent is dispersed and piled inside the tank to form a fixed bed (the height of the bed is 2 / 3 of the height of the tank).

[0076] The above-mentioned adsorbent is a blend of modified attapulgite and modified zeolite, prepared by the following method:

[0077] S1. 70 parts of attapulgite clay (40 mesh) and 20 parts of mordenite zeolite (10 nm) were pretreated with acid and washed with water before use. They were then mixed with a 20 wt% sulfuric acid solution and an 80 wt% acetic acid solution at a mass ratio of 1:1.5, completely soaking the attapulgite clay and mordenite zeolite. The mixture was heated to 75°C and thoroughly mixed for 30 min. After filtration, the mixture was washed with distilled water until neutral and dried for 2 h. Then, 10 parts of 30 wt% silica sol and 15 parts of nano-carbon powder were added and mixed evenly. The mixture was then fed into a twin-screw extruder and extruded at high temperature. The resulting strip material was cut into regular cylinders with a diameter of 5 mm and a length of 5 mm. Finally, the cylinders were calcined in a muffle furnace at 410°C for 4 h to obtain intermediate product 1.

[0078] S2. Wash the intermediate product 1 with deionized water, then immerse 1 part of the intermediate product 1 in 100 parts of NaOH / H2O2 mixed solution, heat and stir under reflux at 80°C for 2 hours, filter, wash with ethanol and deionized water, and vacuum dry at 70°C for 8 hours to obtain the surface hydroxylated modified intermediate product 2.

[0079] S3. The product from step S2 is immersed in a carboxymethyl cellulose solution (50 wt%), heated to 85°C and sonicated for 3 hours, and then washed and dried with water and ethanol to obtain the adsorbent.

[0080] Both the adsorption tank and the decolorization reaction tank operate at room temperature and pressure without the need for additional heating.

[0081] In the NaOH / H2O2 mixed solution, the concentrations of NaOH and H2O2 are 0.5 wt% and 2 wt%, respectively.

[0082] The specific decolorization process is as follows:

[0083] F1. Adsorption of solid carbides and metal ions: The material in the bottom reactor is transported from top to bottom through the fixed bed of the above adsorption tank by a transfer pump, and the residence time is 1 hour.

[0084] F2. Removal of carbonyl compounds: The material after passing through the adsorption tank enters the decolorization reaction tank. When the liquid level in the tank reaches 2 / 3 of the height, a freshly prepared saturated sodium bisulfite solution (40wt%) is added to the decolorization reaction tank at a ratio of 10wt% of the material in the bottom of the tower. The solution is then thoroughly mixed with the material. After 5 minutes, the decolorized mixture is sent to the phase separator for oil-water separation. The aqueous phase is discharged, and the wastewater is sent to the wastewater treatment system. The decolorized oil phase material is directly returned to the bottom of the tower.

[0085] Example 3

[0086] The adsorbent preparation method and material decolorization process in Example 3 are the same as those in Example 1. The only difference is that the calcination temperature in the adsorbent preparation process of Example 3 is 300℃ and the calcination time is 4h.

[0087] Comparative Example 1

[0088] The adsorbent preparation method and material decolorization process of Comparative Example 1 are the same as those of Example 1. The only difference is that no nano carbon powder is added during the adsorbent preparation process in Comparative Example 1.

[0089] Comparative Example 2

[0090] The adsorbent preparation method and material decolorization process of Comparative Example 2 are the same as those of Example 1. The only difference is that the adsorbent preparation process in Comparative Example 2 does not include steps S2-S3.

[0091] Comparative Example 3

[0092] The adsorbent preparation method and material decolorization process of Comparative Example 3 are the same as those of Example 1. The only difference is that saturated sodium bisulfite solution is not added to the decolorization reaction tank in Comparative Example 3.

[0093] Test Results

[0094] The decolorization processes of Examples 1-3 and Comparative Examples 1-3 were tested, specifically by comparing the color of the materials before and after decolorization and calculating the decolorization rate. The test results are shown in Table 1.

[0095] Table 1. Decolorization results of Examples 1-3 and Comparative Examples 1-3

[0096]

[0097] From Table 1, we can conclude that:

[0098] The adsorbent preparation methods and decolorization processes in Examples 1-3 are basically the same, with only slight differences in the raw material ratio and calcination temperature of the adsorbent. After decolorization, the decolorization rate of the bottom material in the three examples is greater than 80%, and the appearance color is significantly improved. This shows that the technical solution provided by the present invention has obvious advantages.

[0099] In Comparative Example 1, the decolorization rate of the bottom material decreased when no nano-carbon powder was added during the preparation of the adsorbent, indicating that the adsorption performance of the compound adsorbent is closely related to its pore structure. Nano-carbon powder can improve the pore structure of the adsorbent by acting as a pore-forming agent. The adsorbent obtained without adding nano-carbon powder had poor decolorization effect.

[0100] In Comparative Example 2, since the adsorbent was not modified with cellulose, its adsorption capacity for organic matter and metal ions was significantly reduced, resulting in a significantly poorer decolorization effect.

[0101] In Comparative Example 3, no saturated sodium bisulfite solution (greater than 40 wt%) was added to the decolorization reaction vessel. The carbonyl compounds that produced color in the bottom material could not undergo nucleophilic addition reactions and remained in the material, resulting in a low decolorization rate.

[0102] In summary, the compound adsorbent and color treatment method used in this invention exhibit good decolorization effect in the ethyl acetate color treatment process. Compared with other comparative examples, the ethyl acetate color treatment method of this invention results in a higher decolorization rate of the bottom reactor material after using ethyl acetate, demonstrating promising application prospects and potential for widespread application in ethyl acetate production processes.

[0103] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, it is intended that all variations falling within the meaning and scope of equivalents of the claims be included within the present invention.

[0104] Furthermore, it should be understood that although this specification describes embodiments, not every embodiment contains only one independent technical solution. This narrative style is merely for clarity. Those skilled in the art should consider the specification as a whole, and the technical solutions in each embodiment can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.

Claims

1. A method for color treatment of ethyl acetate, characterized in that, The material is treated with an adsorbent in an adsorption tank, and then decolorized to obtain the finished product. The adsorbent is a blend of modified attapulgite and modified zeolite. The adsorbent is prepared by the following method: S1. The blend of attapulgite and zeolite is immersed in a solution of sulfuric acid and acetic acid, then washed and dried, and then blended and shaped by an extruder and calcined at high temperature to obtain intermediate product 1. S2. After washing the intermediate product 1, it is immersed in a mixed solution of sodium hydroxide and hydrogen peroxide, heated and stirred, washed and dried to obtain the surface-hydroxylated intermediate product 2. S3. Immerse intermediate product 2 from step S2 in a carboxymethyl cellulose solution, heat and sonicate, and wash and dry to obtain the adsorbent. In the decolorization process, sodium bisulfite solution is used to react with impurities in the material. The sodium bisulfite solution is a saturated solution; The adsorbent also includes silica sol and nano carbon powder.

2. The ethyl acetate color treatment method according to claim 1, characterized in that, The mass ratio of sulfuric acid to acetic acid is 1:1 to 1:

3.

3. The ethyl acetate color treatment method according to claim 1, characterized in that, The attapulgite has a particle size of 40-60 mesh; the zeolite has a particle size of 0.5-20 nm.

4. The ethyl acetate color treatment method according to claim 1, characterized in that, The mass ratio of attapulgite to zeolite is 2-4:

1.

5. The ethyl acetate color treatment method according to claim 1, characterized in that, The intermediate product is a cylinder with a diameter of 5 mm and a length of 5-10 mm.

6. The ethyl acetate color treatment method according to claim 1, characterized in that, The high-temperature calcination temperature is 250-550℃, and the time is 2-6 h.

7. The ethyl acetate color treatment method according to claim 1, characterized in that, The mass ratio of the sodium bisulfite solution to the material is 0.1:10 to 1:10.

Citation Information

Patent Citations

  • Attapulgite clay decolorizing adsorbent for used oil regeneration and preparation method

    CN107597057A

  • Removal of carbonyl impurities from alpha, beta-unsaturated carboxylic acids

    CN1126197A

  • Method for treating and reusing waste fluid from citric acid chromatography extraction

    CN102942236A

  • Attapulgite-based water pollution treatment adsorbent and preparation method thereof

    CN116920790A